Avaliação da gestão dos resíduos sólidos de serviços de saúde em hospitais do município de João Pessoa-PB - Araújo, Elizabeth Sousa de (2018)
Health-Care Waste (HCW) management seeks to adapt handling procedures to legal and regulatory requirements based on waste segregation and reduce the generation. The HCW are those generated in establishments providing aid to human and animal health and although it represents a small percentage of the total solid waste generated in a municipality, it constitutes a portion that represents a risk to human health and the environment when handled in an inadequate manner. With the objective of evaluating the conditions of HCW management, including the steps of segregation, identification, internal transportation, treatment and final destination, a study was carried out on a sample of 18 hospital establishments located in the city of João Pessoa / PB, those 18 establishments correspond to 72.6% of the existing beds in the State. The facilities of two incinerators located in the State of Paraíba were visited for this study. Interviews were conducted in which managers of health-care centers answered a questionnaire prepared and later approved by the Research Ethics Committee of the Lauro Wanderley University Hospital (nº. 2.101.418), and the waste management steps evaluated from a checklist. The results showed that the main difficulties were the incorrect segregation of HCW groups and subgroups; the unfulfillment of elaboration of a health services waste management plan; the wrong storage of infectious waste; the structural deficiencies on the external waste warehouses. In relation to external collection, common wastes were collected by the public cleaning agency and association of recyclable materials. On the other hand, the collection of Groups A, B and E was, in all cases, outsourced and performed by a company specialized in the treatment of HCW. The priority treatment was the incineration and disposal of the ash occurred at Campina Grande Municipal Landfill and at the Waste Treatment Plant of Pernambuco. It is concluded that despite the observation of adequate practices in the intra-establishment management and correct final destination of the infectious and piercing parcel of waste, hospitals must still move forward in order to obtain an adequate situation of the establishments located in the municipality besides the need to improve the data base, mainly in relation to the quantity of waste generation.